牙弓/牙槽骨弓的塑形矫治——基于牙弓形态发育不良的儿童错 [Image: see text] 畸形诊断与阻断治疗 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2016)
The etiology of malocclusions basically involves both congenital and environmental factors. Malocclusion is the result of the abnormal development of the orofacial complex (including tooth, dental alveolar bone, upper and lower jaws). Early orthodontic interceptive treatments involve the elimination of all congenital and environmental factors that contribute to the malformation of the orofacial complex, as well as interrupt the deviated development of the orofacial complex and the occlusion. Early orthodontic interceptive treatments mainly aim to use children's growth potential to correct abnormal developments of occlusions and orthodontically treat malocclusions more efficiently. The early orthodontic interceptive treatments include correcting the child's bad oral habits, training the abnormal functioned para-oral muscles, maintaining the normal eruptions of succeeding permanent teeth, applying interceptive treatments to the mal-developed teeth, and employing functional orthopedic treatments for abnormal growths of the upper and lower jaws. In orthodontics, correcting mal-positioned teeth is called orthodontic treatment, while rectifying the abnormal relationships of the upper and lower jaws is called functional orthopedic treatment. However, no clear definition is available as regards to the early orthodontic interceptive treatment of malocclusions caused by the deviated development of the dental alveolar bone. This new theory of “early dental alveolar bone and dental arch remodeling technique” was proposed by Professor Li Xiaobing of the Department of Pediatric Dentistry, Faculty of Pediatric Dentistry and Orthodontics in West China Hospital of Stomatology through his clinical analyses and investigation of his early orthodontic interceptive treatments. He defined the early orthodontic corrections of abnormal growth of dental alveolar bone as “remodel”. The “early dental alveolar bone and dental arch remodeling theory and technique” is proved useful in malocclusion diagnosis and treatment planning during early orthodontic interceptive treatment with malformed dental arch. With the development of the theory and technique, the author intended to prevent and intercept the malocclusion development more effectively and efficiently. This review presents the development and clinical usages of the theory which to provide a new vision in the analysis of malocclusions on the basis of the developmental mechanism of the alveolar bone and dental arch. With clinical case illustration, the author demonstrateshis successful orthodontic clinical practices with this theory, which may contribute to the development of contemporary orthodontic theories and techniques.